Short-term dietary reduction of branched-chain amino acids reduces meal-induced insulin secretion and modifies microbiome composition in type 2 diabetes: a randomized controlled crossover trial - Karusheva, Yanislava; Koessler, Theresa; Strassburger, Klaus; Markgraf, Daniel; Mastrototaro, Lucia; Jelenik, Tomas; Simon, Marie-Christine; Pesta, Dominik; Zaharia, Oana-Patricia; Bódis, Kálmán; Bärenz, Felix; Schmoll, Dieter; et al. (The American journal of clinical nutrition, 2019)
ABSTRACT Background Epidemiological studies have shown that increased circulating branched-chain amino acids (BCAAs) are associated with insulin resistance and type 2 diabetes (T2D). This may result from altered energy metabolism or dietary habits. Objective We hypothesized that a lower intake of BCAAs improves tissue-specific insulin sensitivity. Methods This randomized, placebo-controlled, double-blinded, crossover trial examined well-controlled T2D patients receiving isocaloric diets (protein: 1 g/kg body weight) for 4 wk. Protein requirements were covered by commercially available food supplemented ≤60% by an AA mixture either containing all AAs or lacking BCAAs. The dietary intervention ensured sufficient BCAA supply above the recommended minimum daily intake. The patients underwent the mixed meal tolerance test (MMT), hyperinsulinemic-euglycemic clamps (HECs), and skeletal muscle and white adipose tissue biopsies to assess insulin signaling. Results After the BCAA− diet, BCAAs were reduced by 17% during fasting (P < 0.001), by 13% during HEC (P < 0.01), and by 62% during the MMT (P < 0.001). Under clamp conditions, whole-body and hepatic insulin sensitivity did not differ between diets. After the BCAA− diet, however, the oral glucose sensitivity index was 24% (P < 0.01) and circulating fibroblast-growth factor 21 was 21% higher (P < 0.05), whereas meal-derived insulin secretion was 28% lower (P < 0.05). Adipose tissue expression of the mechanistic target of rapamycin was 13% lower, whereas the mitochondrial respiratory control ratio was 1.7-fold higher (both P < 0.05). The fecal microbiome was enriched in Bacteroidetes but depleted of Firmicutes. Conclusions Short-term dietary reduction of BCAAs decreases postprandial insulin secretion and improves white adipose tissue metabolism and gut microbiome composition. Longer-term studies will be needed to evaluate the safety and metabolic efficacy in diabetes patients. This trial was registered at clinicaltrials.gov as NCT03261362.